peran PAI dalam membangun moderasi beragama di Indonesia - fatrah; Eko Nursalim (Jurnal Kajian Islam dan Sosial Keagamaan, 2024)
This study aims to explore the role of Islamic Religious Education (PAI) in fostering religious moderation in Indonesia, a country rich in ethnic, cultural, and religious diversity. Utilizing a qualitative approach, this research analyzes the PAI curriculum, teaching methods, and community involvement in cultivating tolerant attitudes among students. The findings indicate that an inclusive curriculum and interactive teaching methods, such as discussions and role-playing, are effective in internalizing the values of religious moderation. Furthermore, community involvement, including the role of religious gatherings and the use of technology, such as social media, also contributes to reinforcing the message of moderation. Although challenges such as intolerant attitudes persist, collaboration among the government, educational institutions, and society is essential to create a supportive educational environment for religious moderation. This research is expected to contribute to the development of a more effective and inclusive PAI, as well as strengthen interfaith harmony in Indonesia.